2018
DOI: 10.1002/2017gc007344
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism at Depth: A View from an Ancient Continental Subduction and Collision Zone

Abstract: Recent sophisticated global data compilations and magnetic surveys have been used to investigate the nature of magnetization in the lower crust and upper mantle. Two approaches to constraining magnetizations are developed, providing minimum (0.01 SI) and maximum (0.04 SI) susceptibility estimates, given some assumed thickness (15+ km here). These values are higher than are found in many continental rocks. Are there rocks deeper in the crust or upper mantle that are more magnetic than expected, or are the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 88 publications
0
16
0
1
Order By: Relevance
“…For example, an extensive study of rocks from the Western Gneiss Region of Norway (McEnroe et al, ), which has a large satellite magnetic anomaly, revealed a wide range of metamorphism and magnetic properties that are mostly weaker than is required to explain the observed anomalies. McEnroe et al () placed bounds on susceptibilities for the lower crust and upper mantle of 0.01 and 0.04 SI assuming a 15‐km‐thick layer, which translates to a VIM of 6 to 24 kA. These are comparable with our values but too small for a magnetized dipping slab.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an extensive study of rocks from the Western Gneiss Region of Norway (McEnroe et al, ), which has a large satellite magnetic anomaly, revealed a wide range of metamorphism and magnetic properties that are mostly weaker than is required to explain the observed anomalies. McEnroe et al () placed bounds on susceptibilities for the lower crust and upper mantle of 0.01 and 0.04 SI assuming a 15‐km‐thick layer, which translates to a VIM of 6 to 24 kA. These are comparable with our values but too small for a magnetized dipping slab.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies by Warner and Wasilewski (), Wasilewski and Warner (), and Wasilewski and Mayhew () report the lithospheric mantle to be too hot and too weakly magnetic to contribute to long‐wavelength anomalies. However, more recent studies propose a potential magnetic contribution from parts of the upper mantle and/or the lower crust (Blakely et al, ; Ferré et al, , ; Friedman et al, ; McEnroe et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Magnetite is usually considered the predominant magnetic mineral in the deep crust (e.g., Frost & Shive, ; Pilkington & Percival, ; Schlinger, ). However, the hematite‐ilmenite solid solution should also be considered as stable sources of remanent magnetization (Robinson et al, ) and as a source for short‐ and long‐wavelength anomalies (Brown & McEnroe, ; Kasama et al, ; Kletetschka & Stout, ; McEnroe & Brown, ; McEnroe et al, , , , , , , , ). The high stability and unblocking temperatures of exsolved phases in the hematite‐ilmenite system increase the remanent contribution to the total magnetization (McCammon et al, ; McEnroe & Brown, ; McEnroe et al, , , , , , ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations